2007
DOI: 10.1016/j.brainres.2007.03.040
|View full text |Cite
|
Sign up to set email alerts
|

A mismatch negativity study of local–global auditory processing

Abstract: We used mismatch negativity (MMN) to examine structural encoding of local and global auditory patterns in perceptual memory. Unlike previous MMN studies of local-global auditory perceptual organization that used interval-contour stimuli, here we presented hierarchical stimuli in which local pattern organization formed global patterns. Importantly, our stimuli allowed independent manipulation of the two structural levels. In separate blocks, participants were exposed to frequent local standard patterns and rare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 45 publications
1
14
1
Order By: Relevance
“…Our failure to find processing asymmetries for fast or slow temporal ranges converges with previous ERP studies using similar hierarchical stimuli (List et al, 2007;Sanders & Poeppel, 2006). However, it conflicts with the notion that the hemispheres are inevitably asymmetrically recruited for temporal processing.…”
Section: Discussioncontrasting
confidence: 35%
See 1 more Smart Citation
“…Our failure to find processing asymmetries for fast or slow temporal ranges converges with previous ERP studies using similar hierarchical stimuli (List et al, 2007;Sanders & Poeppel, 2006). However, it conflicts with the notion that the hemispheres are inevitably asymmetrically recruited for temporal processing.…”
Section: Discussioncontrasting
confidence: 35%
“…Recently, we employed the Fast-Slow Stimuli in an electrophysiology experiment of implicit local-global processing, using a mismatch negativity design (List, Justus, Robertson & Bentin, 2007). Conceding that event-related potentials (ERPs) are perhaps not best-suited to detect lateralization of function, we failed to find any evidence for asymmetric local-global processing.…”
Section: Discussionmentioning
confidence: 90%
“…Early in the sense that MMN peaks prior to non-modality-specific attention-related ERP components (e.g., N2b and P3b components), and that MMN elicitation is not dependent upon attention-related components to be elicited. However, MMN may be thought of as a relatively late occurring process in the sense that other processes precede deviance detection, relevant to establishing the standard either by stimulus-driven or top-down processing (List et al, 2007; Sussman, 2005; Sussman, 2007; Sussman et al, 2002; Panesse et al, submitted; Sussman, Ritter, Vaughan, 1998a; Sussman, Ritter, Vaughan, 1998b; Sussman, Bregman, et al, 2005; Sussman, 2005; Müller et al, 2005; Nager et al, 2003; Winkler et al, 2005; Yabe et al, 2001). MMN elicitation may also be considered a ‘late’ process for the auditory system because it has been shown to be more closely linked to task goals, to behavioral performance, than earlier elicited components or to the later P3a component (e.g., Tiitinen et al, 2004; Chen & Sussman, 2013).…”
Section: Five Myths Of Mmnmentioning
confidence: 99%
“…In the study by Tervaniemi et al (1994), both the ascending and the repeated tone elicited a mismatch response when presented after the series of descending Shepard tones suggesting that violations of higher-order rules are preattentively encoded. Similarly, in an EEG study where both local and global stimulus features were manipulated, MMN was mainly observed for global deviation (List et al, 2007). The extraction of abstract features goes beyond frequency-based rules as demonstrated by a further EEG study (Paavilainen et al, 2003).…”
Section: Introductionmentioning
confidence: 96%